No country for Black men - Ball, Roger, 1975- (Emerald Publishing Limited : Information Age Publishing, Inc., 2023)
"No Country For Black Men captures the plight and possibilities of what it means to be Black and male in the United States past and present. Through storytelling, sociological data analysis, the author weaves a powerful story about challenges and opportunities faced by Black males of all ages today. From mental health parity to disproportionality and myths about Black male sexuality, this body of work is bent on naming the persistent and historical challenges Black men are confronted with throughout their development. Each chapter is anchored in and punctuated by the author's personal experiences as an immigrant, a father, a husband and a scholar-practitioner. The mission of No Country For Black Men is to add to the scholarship and conversation among educators, mental health providers, religious leaders, and other service providers about ways to improve the academic, economic and health outcome for Black males in the United States"--